224 Person-related factors associated with work participation in employees with health problems: a systematic review. (24th April 2018) - de Wit, M; Wind, H; Hulshof, CTJ; Frings-Dresen, MHW
Abstract : Introduction: Sick leave or work disability, is a major health problem, with negative consequences for the employee, employer and society. In order to prevent or decrease the duration of sick leave, it is important to know which factors influence work participation. Research revealed that besides disease-related factors, person-related factors like cognitions and perceptions of employees play a role in work retention and return to work after sick leave. Structured information about these factors can help occupational- and insurance physicians in their activities to decrease the duration of sick leave. However, structured information about the influence of person-related factors on work participation of workers with health problems is not available yet. This study aims to provide systematically assessed information about the association between person-related factors and work participation. Methods: A systematic review was conducted to explore the association between person-related factors and work participation. PubMed and PsycINFO were used to search for papers published between January 2007 and February 2017. There were no restrictions in study design. The methodological quality of included studies was assessed using quality assessment tools of the Joanna Briggs Institute. Result: 116 of 3465 studies were included which addressed the association between person-related factors and work participation. Evidence was found for a positive association between motivation, positive recovery expectations, self-efficacy, intern locus of control, perceived health, and optimism and work retention or return to work after sick leave. The person-related factors catastrophizing, fear-avoidance coping, and perceiving work as a cause of the disability were negatively associated with work retention or return to work after sick leave. Discussion: The results provide input for developing tailored interventions and provide guidance for occupational- and insurance physicians to facilitate returning to work and work retention. Further research is required to determine how these physicians could acquire and apply information about person-related factors.